The challenge of fifth generation R&D - Rogers, Debra M. Amidon
Debra M. Amidon Rogers calls for innovation systems that optimize knowledge (not information) flows through networks that include customers, suppliers, distributors and other stakeholders.
Technology leaders will need to develop innovation systems that optimize knowledge flows through collaborative, networked groups in virtual organizations.
Economic, behavioral and technological forces are leading us into an era of knowledge-as opposed to technological-innovation. Under these conditions, management systems must be viewed holistically in order to optimize the creation and movement of ideas into the marketplace expeditiously and profitably. There will be a fundamental shift toward virtual, networked organizations that transcend conventional boundaries. These new collaborative learning systems will enable the flow of knowledge-not information-throughout the organization, now redefined to include customers, suppliers, distributors and other stakeholders. The resulting challenge to top management : Who will be the chief innovation officer of your enterprise?
Keywords: R&D.